Adlafia sinensis sp. nov. (Bacillariophyceae) from the Wuling Mountains Area, China, with reference to the structure of its girdle bands - Liu, Bing; Williams, David M.; Ou, Yongda (Phytotaxa, 2017)
Adlafia sinensis sp. nov., a new diatom species from the Wuling Mountains Area, China, has been studied using light and scanning electron microscopy. The valves are lanceolate with rostrate to subcapitate apices; the areolae are occluded by hymens outside and the both terminal raphe fissures hook towards the secondary side; the mantle is deep with c. 5–7 isolated striae not continuous from the valve face. Only one girdle band (valvocopula) occurs between the epivalve and hypovalve except at the apices of each frustule. The nature of the valvocopula is open because the two parts are not fused together. A. sinensis is compared with the all species in the genus Adlafia. A. sinensis is epilithic and live in freshwater habitats.